Economics of cancer related medical care: Worldwide estimates and available domestic evidence - Radovanović Ana; Dagović Aleksandar; Jakovljević Mihajlo (Archive of Oncology, 2011)
Background: The aims of this article were to report findings of domestic research related to assessment of hospital treatment costs of Serbian patients suffering from cancer and show similar study results among foreign trials. The authors also intended to suggest likely strategies to improve local cost containment in future. Cost-of-illness studies of most high-income economies have proven that malignant disorders belong to top five disorders according to their overall financial burden. Methods: Our trial was conducted as an in depth, retrospective, bottom-up, trend analysis of services consumption patterns and expenses relative to diagnosis at discharge, from perspective of the third party payer. Discounting rates were calculated according to the average official exchange rates of the National Bank of Serbia in respective years. Financial value of medical goods and services consumed was taken out of current price lists of the National Republic Institute on Health Insurance on a day when particular service was provided. Results: There were 434 patients and 4850 admissions processed in 2007, consuming 48,483,740.49 RSD (€613,562.90) while in 2010 there were 539 patients and 9509 admissions, consuming 68,880,953.27 RSD (€658,832.65). In total, drugs value accounts for only 5%, radiotherapy 54% and the rest of expenditure 41% (consultations, surgery, consumables, nursing care, other). Average overall cost per patient treated was 125,922.34 RSD and per hospital admission, it was 8,297.99 RSD. Cancer-related medical care costs, in domestic currency, increased by almost one third in only four-year time span. Conclusion: Higher awareness of clinicians on cost limitations and necessity of prioritization in funding health care, would provide wiser resource allocation and more care with money available.